2012
DOI: 10.1037/a0025180
|View full text |Cite
|
Sign up to set email alerts
|

What's social about social learning?

Abstract: Research on social learning in animals has revealed a rich variety of cases where animals--from caddis fly larvae to chimpanzees--acquire biologically important information by observing the actions of others. A great deal is known about the adaptive functions of social learning, but very little about the cognitive mechanisms that make it possible. Even in the case of imitation, a type of social learning studied in both comparative psychology and cognitive science, there has been minimal contact between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
394
0
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(430 citation statements)
references
References 82 publications
23
394
0
13
Order By: Relevance
“…Recent studies have shown that social learning in rats can be influenced by early developmental cues such as maternal care (Lindeyer et al 2013), and in bees by past learning histories (Dawson et al 2013). However, while similar processes may well operate in humans (Heyes 2012), it is difficult to explain the species differences in cumulative cultural evolution described above without positing some kind of genetic adaptation in the human lineage, perhaps involving the extent of imitation during childhood (Lyons et al 2007) or theory of mind (Tomasello et al 2005). …”
Section: Are Social Learning Biases Learned or Innate?mentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies have shown that social learning in rats can be influenced by early developmental cues such as maternal care (Lindeyer et al 2013), and in bees by past learning histories (Dawson et al 2013). However, while similar processes may well operate in humans (Heyes 2012), it is difficult to explain the species differences in cumulative cultural evolution described above without positing some kind of genetic adaptation in the human lineage, perhaps involving the extent of imitation during childhood (Lyons et al 2007) or theory of mind (Tomasello et al 2005). …”
Section: Are Social Learning Biases Learned or Innate?mentioning
confidence: 94%
“…In the non-human literature, too, it has been argued that social learning can be explained in terms of simple associative learning mechanisms, rather than dedicated geneticallyspecified, domain-specific mechanisms (Heyes 2012;Heyes and Pearce 2015;Leadbeater 2015). Recent studies have shown that social learning in rats can be influenced by early developmental cues such as maternal care (Lindeyer et al 2013), and in bees by past learning histories (Dawson et al 2013).…”
Section: Are Social Learning Biases Learned or Innate?mentioning
confidence: 99%
“…It is also a much faster and much more reliable way of acquiring solutions than asocial exploration and learning, making it an energetically vastly more efficient use of expensive brain tissue. Finally, selection on more effective techniques of social learning also automatically improves the asocial learning ability because of the high cognitive overlap between the two [56]. This overlap also ensures correlated evolution between innovative and social-learning abilities.…”
Section: Domain-specific or Domain-general Cognitive Abilities?mentioning
confidence: 99%
“…These principles have been used with great success to account for the phenomena of asocial learning [4], and can account for many aspects of social learning [5,6]. Moreover, the formal manner in which the principles have been presented means that it is possible to derive clear predictions from them concerning the various SLSs considered below.…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomies of this kind typically delineated social learning effects, not social learning mechanisms; they focused on the behavioural products of social learning, but were silent about the psychological (and neurological) processes yielding these outcomes [5].…”
Section: Introductionmentioning
confidence: 99%